2009
DOI: 10.1007/s11579-009-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Representation results for law invariant time consistent functions

Abstract: We show that the only dynamic risk measure which is law invariant, time consistent and relevant is the entropic one. Moreover, a real valued function c on L ∞ (a, b) is normalized, strictly monotone, continuous, law invariant, time consistent and has the Fatou property if and only if it is of the form c(X) = u −1 •E [u(X)], where u : (a, b) → R is a strictly increasing, continuous function. The proofs rely on a discrete version of the Skorohod embedding theorem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 30 publications
3
83
0
1
Order By: Relevance
“…Nevertheless, it appears that the solvency capital obtained can be very expensive if we do not take care of the confidence level of each conditional VaR and TVaR measures involved in the iteration scheme. This is linked to a result obtained in [13], which tells us that, under certain hypotheses, if we consider a great number of iterations, the risk measure obtained is close to either the conditional expectation of the risk or its essential supremum.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, it appears that the solvency capital obtained can be very expensive if we do not take care of the confidence level of each conditional VaR and TVaR measures involved in the iteration scheme. This is linked to a result obtained in [13], which tells us that, under certain hypotheses, if we consider a great number of iterations, the risk measure obtained is close to either the conditional expectation of the risk or its essential supremum.…”
Section: Introductionsupporting
confidence: 52%
“…We consider here T iterations, i.e., a finite number of steps t ∈ T (see Corollary 1), while in ( [13] [Theorem 1.10]) they consider an infinite (but still countable) number of iterations, i.e., t ∈ N. However, depending on the choice of the dynamic risk measure and on the actual final net worth considered, a great number of iterations T could converge towards ( [13] [Theorem 1.10]), which is the case in [10][11][12].…”
Section: Compositions Of Conditional Risk Measuresmentioning
confidence: 99%
“…Investigation of the use of entropic risk measures of the form suggested by Kupper and Schachermayer (2009) also bears further investigation. These risk measures are time consistent but not scale invariant.…”
Section: Modeling Considerations and Concluding Remarksmentioning
confidence: 99%
“…Kupper and Schachermayer (2009) have shown that a certain class of "entropic" risk measures are the only possible ones that are both time consistent and law invariant. While use of such risk measures definitely warrants further study, they are are not coherent, failing to meet the scale-invariance property of coherent risk measures (see below).…”
Section: Introductionmentioning
confidence: 99%
“…In continuous time such strongly time consistent versions do not even exist, cf. Kupper and Schachermayer (2009) and Delbaen (2006).…”
mentioning
confidence: 99%